2013
DOI: 10.1210/jc.2012-3453
|View full text |Cite
|
Sign up to set email alerts
|

Early Development of Hyperparathyroidism Due to Loss ofPTHTranscriptional Repression in Patients With HNF1β Mutations?

Abstract: Our data demonstrate that HNF1β is a novel repressor of human PTH gene transcription, which could contribute to the development of hyperparathyroidism in patients with HNF1β mutations or deletions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The prevalence of hypomagnesemia ranges from 0 to 100% in the different studies, but the prevalence in adults is consistently higher in those studies that included children and adults. 43,44,49 The same appears to be true with regard to the extrarenal phenotypes of elevated liver enzymes, pancreatic hypoplasia, and diabetes mellitus. These differences might be related to a delayed onset of the phenotypical changes.…”
Section: Epidemiologymentioning
confidence: 80%
See 2 more Smart Citations
“…The prevalence of hypomagnesemia ranges from 0 to 100% in the different studies, but the prevalence in adults is consistently higher in those studies that included children and adults. 43,44,49 The same appears to be true with regard to the extrarenal phenotypes of elevated liver enzymes, pancreatic hypoplasia, and diabetes mellitus. These differences might be related to a delayed onset of the phenotypical changes.…”
Section: Epidemiologymentioning
confidence: 80%
“…42 Early Onset Hyperparathyroidism Ferrè et al observed early hyperparathyroidism and parathyroid hormone (PTH) levels that were judged inappropriately high relative to kidney function in several patients with known HNF1B mutations or deletions. 43 HNF1b was demonstrated to be expressed by PTHproducing parathyroid gland cells. 43 Wild-type HNF1b inhibited transcription of the PTH gene, thus functioning as a transcriptional repressor of PTH production.…”
Section: Mental Retardation and Autismmentioning
confidence: 98%
See 1 more Smart Citation
“…In a recent report of a single-centre cohort of ten HNF1B mutation carriers with available parathyroid hormone (PTH) plasma levels, seven had CKD stage <3 [glomerular filtration rate (GFR)>60 ml/min/1.73 m 2 based on either estimated or measured creatinine clearances], yet elevated PTH levels (6.6-16.3 pmol/l, normal <6.5) [52]. One of these patients had a diagnosis of primary hyperparathyroidism with parathyroidectomy at age 23 years, several years before the HNF1B mutation was identified.…”
Section: Primary Hyperparathyroidismmentioning
confidence: 99%
“…One of these patients had a diagnosis of primary hyperparathyroidism with parathyroidectomy at age 23 years, several years before the HNF1B mutation was identified. The group subsequently identified an HNF1B-responsive element in the PTH promoter and demonstrated repression of PTH transcription by HNF1B [52]. The elevated PTH levels were made more remarkable by the fact that six of these seven patients had concomitant hypomagnesaemia (0.41-0.64 mmol/l): hypomagnesaemia is usually associated with hypoparathyroidism, as magnesium is an important cofactor for the calcium-sensing receptor to initiate PTH release [53].…”
Section: Primary Hyperparathyroidismmentioning
confidence: 99%